2016
DOI: 10.18632/oncotarget.11789
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-sensitive composite hydrogels based on poloxamer 407 and alginate and their therapeutic effect in embolization in rabbit VX2 liver tumors

Abstract: Interventional embolization therapy is an effective, most widely used method for inoperable liver tumors. Blood-vessel-embolic agents were essential in transarterial embolization (TAE). In this work, thermo-sensitive composite hydrogels based on poloxamer 407, sodium alginate, hydroxymethyl cellulose and iodixanol (PSHI), together with Ca2+ (PSHI-Ca2+) were prepared as liquid embolic agents for TAE therapy to liver cancer. With increasing temperature, PSHI exhibited two phase states: a flowing sol and a shrunk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…Preparation of PF/GAG@BSA hydrogels PF/GAG composite hydrogels were prepared according to a previously reported cold method [19,20]. Briefly, 2 g PF127 and 0.05 g GAG for each formulation was added into 7.95 g sterilized ultrapure water and stirred overnight at 4 C until the homogeneous and clear solution is obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Preparation of PF/GAG@BSA hydrogels PF/GAG composite hydrogels were prepared according to a previously reported cold method [19,20]. Briefly, 2 g PF127 and 0.05 g GAG for each formulation was added into 7.95 g sterilized ultrapure water and stirred overnight at 4 C until the homogeneous and clear solution is obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Besides, they can be self-administered without partner knowledge. Several studies have been focused on the formulation of viscoelastic and temperature-sensitive hydrogels based on poloxamer 407, with remanence capacity at the vaginal mucosa and sufficient resistance to dilution in presence of vaginal fluids (Aka- Any-Grah et al, 2010;Huang et al, 2016;Liu et al, 2009). In aqueous solution, this synthetic poly(ethylene oxide)-poly(propylene oxide)poly(ethylene oxide) triblock copolymer forms micelles above a critical micelle concentration or temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a recent study showed that sodium alginate in oil-poloxamer organogels intended for vaginal administration of voriconazole were non-cytotoxic towards HeLa and Vero cell lines (Querobino et al 2019). Huang et al (2016) also reported an absence of cytotoxicity in mouse fibroblast (L929) cell line of thermosensitive composite hydrogels based on poloxamer 407 and alginate used in transarterial embolization therapy. To the best of our knowledge, there is only one published study reporting the use of a gel for the administration of Lactobacilli into the vagina (Vigani et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…PSHI material can be recanalized within 30 min, while PSHI-Ca 2+ hydrogel had a good blocking effect within 7 d and achieved outstanding curative effect in rabbit VX2 liver tumors. [36]…”
Section: Thermosensitive Composite Hydrogel Of Poloxamer 407 and Alginatementioning
confidence: 99%